Detección y desarrollo de talentos para la regionalización - González Riesle, Alvaro (1992)
Through the administration of a tests battery, 35 adolescents with an I.Q. above average were identified. They were all high schools students enrolled in public and private schools, from the City of Tacna. The goal of the study was to promote activities for the identification of talented youngsters that could be stimulated in a proper way in the Region of Tama. Once the identification was made, they were invited with theirparentes, school principals and local authorities to participate in workshops in which the importance of supporting the talented was discussed.